Romantičnost slovenskega "romantičnega" samospeva - Nagode, Aleš (Muzikološki zbornik, 2006)
Author deals with the questionable use of the combination of words ''romantic lied'' as a label for Slovene compositional creativity in this genre in the 19th century. He bases his observation of the Slovene lied on two different understandings of the term ''romanticism'': 1. as a designation of the music written in the period 1820 to 1850; and 2. as a designation of the 19th century music marked by the basic aesthetic idea of a ''romantic surplus'' that shows itself in exceeding the inner as well as formal boundaries valid in music up to that time.
Keywords: 19.st.; Romanticism; romantika; samospev; slovenska glasba; terminologija; terminology